Experimental quantification of interfacial convections at the water–nonaqueous‐phase liquid interface in microfluidic systems - Wismeth, Carina; Flury, Markus; Baumann, Thomas (Vadose zone journal, 2023)
Mass transfer rates at liquid–liquid interfaces are relevant for a broad range of processes in natural and technical systems. The objective of this study was to characterize and quantify convective flow along the interface between water and nonaqueous‐phase liquids (NAPLs). Three NAPLs with different water solubility were used: 1‐heptanol, 1‐octanol, and 1‐nonanol. The convective flow was visualized and recorded in a micromodel setup with fluorescent particles and an epifluorescence microscope. Individual trajectories were evaluated to obtain the statistics of the particle velocities. We observed a fast‐rotating convection current along the NAPL–water interface with a maximum velocity of approximately 1,000 μm s−1 after 10 min. The fluid motion showed a persistent movement in the form of a rolling cell for at least 99 h, but a decreasing rotation speed over time. We attributed the convective flow dynamics to three mechanisms following different kinetic rates: (a) a short‐lived Marangoni flow, (b) a medium‐lived dissolution‐driven flow, and (c) a long‐lived evaporation‐driven flow. Upon initial contact between water and NAPLs, the differences in surface tension caused a rapid Marangoni flow along the interface, which died out quickly as the surface tensions were equilibrated. The Marangoni flow was superseded by a dissolution‐driven flow as the NAPLs dissolved in the aqueous phase. The dissolution‐driven flow dissipated according to a first‐order rate law and died out when the liquids were mutually saturated. Evaporation of water and NAPLs caused a long‐term but slow convective flow. The interaction of these three mechanisms caused enhanced mixing during multiphase transport. Core Ideas Mass transfer across interfaces is strongly affected by interfacial motion Interfacial motion is driven by Marangoni, dissolution‐driven, and evaporation‐driven flow. Enhanced mixing of phases is expected in the vadose zone at nonaqueous‐phase liquid–water interfaces.